Autobiographical memory in borderline personality disorder and depression - Renneberg, Babette; Theobald, Erika; Nobs, Monika; Weisbrod, Matthias (Cognitive therapy and research, 2005)
Responses to an autobiographical memory test (AMT, Williams & Broadbent, 1986) are examined in a sample of 30 female psychiatric inpatients with borderline personality disorder (BPD) in comparison to a group of 27 depressed inpatients and a nonclinical control group of 30 women. Concordant with the literature, depressed patients retrieved fewer specific memories than the control group, generated significantly more categoric memories than participants of both other groups, and needed more time for retrieval. Contrary to expectation, patients with BPD did not differ from normal control participants in specificity, nor latency of their retrieved memories. In both clinical groups, hedonic tone of retrieved memories was more often negative than in the control group. In this sample of inpatients with BPD, specificity of memories was not related to self-reported level of depression, dissociative symptoms, or frequency of self-mutilation.
Gesehen am 22.12.2021